Optical temperature measurement of small droplet array luminous flame in butane diffusion flame - Hiroshi ENOMOTO; Syunsuke SAWASAKI; Hirotaka NOZUE; Naoki IWAFUNE; Noboru HIEDA (Nihon Kikai Gakkai ronbunshu, 2015)
Two color ratio method was applied to measure temperature distributions of a luminous diffusion flame. A small blue butane diffusion flame, 3mm in flame diameter, was used. A small droplets array (300 droplets of 30um in diameter) was injected in the diffusion flame. The component was 85% hexadecane and 15% o-xylene to surrogate diesel oil. A color CMOS high speed camera of 4kpfs in flame speed and 16um/pix in spatial resolution was used to measure the flame shape and the temperature. The flame with the droplet array was luminous and the temperature was measured with optical two color ratio method (green and red). In the two color ratio method, a threshold of the red intensity should be defined. As the flame could be assumed as an axial symmetry, an Abel conversion was used. In the Abel conversion, thresholds of red/green intensities should be defined to form a sextic even polynomial. A thin sheath thermocouple (0.3mm in sheath diameter) was used to compare the two color ratio method results. As a result, the red intensity threshold for the two color method was reasonable and 40 in this experiment. In comparison with a KL value two color method, the two color ratio method could show lower temperature region.